Students evaluation of the performance of the teaching staff of the University of Science and Technology in the light of some teaching competencies - Dawood Al-Hidabi; Khalid Khan (University of Science and Technology, Yemen, 2008)
Abstract                                                                                                                                                       The study aimed at identifying the level of performance of the teaching staff at the Yemeni University of Science and Technology through the students point of view on a number of teaching competencies. For this purpose, the researchers developed a questionnaire composed of 22 items, distributed to 6 teaching competencies which are: teaching, feedback, academic support,   class management, learning resources, and personal development. The total number of the students participating in the evaluation is 6591, representing all the specialties and levels and the number of teachers being evaluated was 102, 88 male and 14 female. Results reveal no significant differences among the teachers mean scores that can be attributed to either qualification or gender at α =0.05. The researchers recommend setting plans necessary to training the teaching staff with regard to teaching, evaluation, academic support, class management, and personal development. They also recommend giving teachers feedback on their evaluation. They replicating the same study considering  other variables.